BISNIS MULTILEVEL MARKETING DALAM PERSPEKTIF ISLAM - Rahmawaty, Anita (EQUILIBRIUM, 2014)
Multilevel marketing is a marketing strategy that utilized customers to promote a certain product using multiple levels. This Approach is popular due to the increasing of the accessibility of modern social networks. However, because of this popularity, this method used to deceived customer, by using MLM they cheat customers so its impact on people distrust. Multilevel marketing often received criticism from the community. This is due to most of the people who pursue MLM is not understand the characteristics of the MLM business as a whole, whether in business it contains elements that is forbidden or not, and whether the business marketing system in accordance with Islamic law. This study examines the foundation for the study of the legal status of the clarity of MLM business in the perspective of Islamic law.Keywords: Multilevel marketing; Business; Islamic lawMultilevel marketing merupakan strategi pemasaran yang memanfaatkan konsumen untuk menyalurkan suatu produk tertentu dengan menggunakan beberapa level. Strategi ini sangat populer karena adanya dukungan akses jaringan sosial modern. Namun demikian, dalam perkembangannya, muncul penipuan bisnis yang berkedok MLM sehingga membuat citra bisnis MLM ini menjadi buruk di mata masyarakat. Akibatnya, bisnis MLM ini sering menerima kritik dari masyarakat. Hal ini disebabkan sebagian besar orang yang berbisnis MLM tidak memahami karakteristik dari bisnis MLM secara keseluruhan, baik apakah dalam bisnis ini mengandung unsur yang dilarang atau tidak, dan apakah sistem pemasaran bisnis ini sesuai dengan hukum Islam. Makalah ini mengkaji tentang kejelasan status hukum bisnis MLM dalam perspektif hukum Islam.Kata Kunci: Multilevel marketing, Bisnis, Hukum Islam